Identification and characterization of microsatellites from the Antarctic isopod Ceratoserolis trilobitoides: nuclear evidence for cryptic species - Leese, Florian; Held, Christoph (Conservation genetics, 2008)
We report the successful isolation of 10 polymorphic microsatellite markers for one species of the marine isopod species complex Ceratoserolis trilobitoides (Eights, 1833) from the Southern Ocean. The number of alleles per locus ranged from 6 to 30 for the 148 specimens analysed and heterozygosity ranged from 0.34 to 0.98. Seven microsatellites amplified successfully in a cryptic sister species, which is restricted to the Antarctic Peninsula. This novel marker set provides the opportunity to study and monitor population structure, demography and gene flow patterns for a benthic model taxon in a region that is now subject to rapid climate change.